Ontologi Islam: Hakekat Ilmu dan Worldview Tauhid Islam serta Implikasinya dalam Pendidikan Agama Islam - Afima, Oby Ara; Amril M (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2025)
This article examines the concept of Islamic ontology as a philosophical foundation for understanding the nature of knowledge and the Islamic monotheistic worldview, as well as its implications for Islamic religious education. Ontology, as a branch of philosophy that discusses the nature of existence, from an Islamic perspective, asserts that everything originates from God as the Obligatory Being, while humans and nature are creations dependent on Him. The nature of knowledge in Islam is not only empirical and rational, but also transcendental, as knowledge is viewed as a divine mandate aimed at bringing humans closer to God and fostering noble morals. The Islamic monotheistic worldview places the oneness of God as the central orientation in the pursuit and development of knowledge, so that knowledge is not neutral, but rather bound to divine values ​​that shape the character, morals, and spirituality of students. This study uses a qualitative method with a library research approach and descriptive-analytical analysis to examine the relationship between ontology, the nature of knowledge, and the monotheistic worldview in Islamic education. The results of the study indicate that Islamic religious education must be understood as a process of developing ontological awareness of monotheism, which integrates knowledge, faith, and morals into one whole. Thus, Islamic education not only functions as a transfer of knowledge but also as a means of tazkiyah (purification of the soul) and the formation of an integral personality (insān kāmil) who can face global challenges while adhering to the value of monotheism. The tawḥīd worldview emphasizes that knowledge must always be tied to divine values, so that no knowledge is free from moral responsibility.